2017
DOI: 10.5812/numonthly.45029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inactive Vitamin D on Persistent Secondary Hyperparathyroidism in Patients on Hemodialysis

Abstract: Background: Secondary Hyperparathyroidism (sHPT) is an important feature of chronic renal failure and contributes to the development of renal osteodystrophy. This study was carried out to assess 25(OH)D status and its effect on sHPT in patients on hemodialysis (HD). Methods: A prospective experimental trial of 180 HD patients (F: 81, M: 99, age > 14year) participated in the study. At base line, levels of 25(OH)D, intact Parathyroid Hormone (iPTH), Calcium (Ca), Phosphorous (P), Alkaline phosphatase (Alk p), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…A hospital based cross-sectional descriptive study was carried out to find out the prevalence of secondary Hyperparathyroidism in chronic renal failure patients. It is one of the leading causes of chronic morbidity and 11,13,14 In this study prevalence of secondary hyperparathyroidism in diabetic patients is 66% and in non-diabetic patients is 73%, that is supported by other study by Arevalo-lorido JC et al, in their study on 407 patients (214 diabetics) hyperparathyroidism was found in 60.4% of diabetic patient's vs 65% of non-diabetic patients. 15 This observation is also supported by Owda A et al, in their study there was no significant difference in serum PTH levels between diabetic and non-diabetic patients.…”
Section: Discussionsupporting
confidence: 81%
“…A hospital based cross-sectional descriptive study was carried out to find out the prevalence of secondary Hyperparathyroidism in chronic renal failure patients. It is one of the leading causes of chronic morbidity and 11,13,14 In this study prevalence of secondary hyperparathyroidism in diabetic patients is 66% and in non-diabetic patients is 73%, that is supported by other study by Arevalo-lorido JC et al, in their study on 407 patients (214 diabetics) hyperparathyroidism was found in 60.4% of diabetic patient's vs 65% of non-diabetic patients. 15 This observation is also supported by Owda A et al, in their study there was no significant difference in serum PTH levels between diabetic and non-diabetic patients.…”
Section: Discussionsupporting
confidence: 81%
“…In HD patients, the lowest level of vitamin D3 was probably attributed to their low activity and not exposure to the sun; since the number of patients on stage 2 was low, we could not rely on this accidental finding. Based on a previous study (19) and our findings, there is an association between serum level of 25(OH) D3 and PTH levels at all stages of CKD; this connection was more obvious in stage 5 CKD patients. It is suggested that, if hyperparathyroidism is detected in CKD patients with vitamin D deficiency, this abnormality should be corrected with hyperparathyroidism control (8).…”
Section: Discussionmentioning
confidence: 99%